Lysis performance of bacteriophages with different plaque sizes and comparison of lysis kinetics after simultaneous and sequential phage addition - Ameh, Ekwu Mark; Tyrrel, Sean; Harris, Jim A.; Pawlett, Mark; Orlova, Elena V.; Ignatiou, Athanasios; Nocker, Andreas (Mary Ann Liebert, 2020)
Background: Although bacteriophages see a revival for specifically removing undesired bacteria, there is still much uncertainty about how to achieve the most rapid and long-lasting clearance. Materials and Methods: This study investigated the lysis kinetics of three distinct environmental coliphages, reproducibly forming different plaque sizes (big, medium, and small). Lysis performance by individual phages was compared with the one obtained after simultaneous or sequential addition of all three phages. Kinetics was monitored by density absorbance or by flow cytometry, with the latter having the advantage of providing higher sensitivity. Results: Plaque size happened to correlate with lysis kinetics in liquid suspensions, with phages producing big (phage B), medium (phage M), and small (phage S) plaques showing maximal bacterial clearance under the chosen conditions within ∼6, 12, and 18 h, respectively. Use of a phage cocktail (all three phages added simultaneously) resulted in slower initial lysis compared with the fastest lysing phage with the greatest plaque size alone, but it showed longer efficacy in suppression. When adding phages sequentially, overall lysis kinetics could be influenced by administering phages at different time points. The lowest bacterial concentration after 36 h was obtained when administering phages in the sequence S, M, and B although this combination initially took the longest to achieve bacterial clearance. Conclusions: Results support that timing and order of phage addition can modulate strength and duration of bacterial suppression and, thus, influence the overall success of phage treatment.
Keywords: phage lysis kinetics; sequential phage application; simultaneous phage application; phage cocktail